Severe atopic dermatitis with xerophthalmia in children: A case report - Sumadiono Sumadiono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
The management of the atopic dermatitis is not easy and in the severe cases it is a chalenge for the physician. It was reported a 6 year and 3 month old boy with severe atopic dermatitis with erythroderma, secondary infection, marasmic type of severe malnutrition with xerophthalmia, suspected iron defeciency anemia, acute gastroenteritis and miliary tuberculosis. The child had suffered from this disease since he was 3 months old, spreading and becoming worse. The clinical manifestations were redness and black appearance of the skin, excoriation and cast in the skin, some pats of the skin chaping and watery, there was a lacerated wound around his nose. There were many relatives with atopic history in his family tree. The patient had allergy to some medicines (ampicillin and sulfa), and also to many kinds of food. There was eosinophilia in the peripheral blood. The patient had been treated with topical skin medicine, systemic antihistamin/corticosteroid, anti tuberculosis, antibiotics, and local treatment for his eyes, but no improvement. According to the discussion between pediatricians and dermatologists the patient was suffered from severe atopic dermatitis, and was suspected had another disease (geno dermatitis). It is important to avoid drugs that had triggerred allergy before. The limitation of the diet had caused severe malnutrtion. Vitamin A had to be given early. Second generation antihistamine was actually needed to be given early and for several months. It was necessary to do many examinations to establish more exact diagnosis, but the patient died before the examinations were done.Keywords : Atopi dermatitis in children - eosinophil - marasmus xerophthalmia - treatment